THE IMPACT OF THE POLITICAL CULTURE IN POLITICAL SYSTEM AND RULE OF LAW: ALBANIA CASE - Mehmetaj, Jonida (European Scientific Journal, ESJ, 2014)
This study will be focused in analyzing on how political culture can impact in the rule of law and political system in Albania. Political system is defined as the interaction between political institutions and political culture. While, the constitution of the legal state is a common responsibility of the citizens, civil society and state institutions. All these three concepts, political culture, political system and rule of law are strongly connected among them; this way political culture will impact in the performance of independent judiciary and political institutions. In case of Albania, there’s a different situation; political culture, yes it can affect but the question is if it improves the performance of these institutions or worsen that. Albanian political culture must be perceived within the context of the historical background, because such periods of time like communist regime, problematic transition (accompanied with civil war on 1997) will have the impact in political and cultural education of the citizen. That will contribute to deepening of subordinated point of view and approaches, subordinated to authorities, non-active civil society, corruption expansion in all governmental structures and so leading to harm of liberal democracy. To this background and political culture, many issues addressed to accountability of political elites in control and responsiveness to the voters will be appeared. Legal accountability, which implicates governing according to the law, equality in the face of law, will be in danger if changes don’t get started with public opinion, education of democratic values, independent judiciary, power division and corruption extinction.